Pengaruh Komunikasi Pimpinan Terhadap Produktivitas Kerja Dan Prestasi Agen Pada PT. Sunlife Financial Cabang Kota Medan - Nawawi, M Iqbal; Lubis, Fauzi Arif; Atika, Atika (Universitas Labuhanbatu, 2023)
A person's work productivity is seen from as he carries out his duties, this is also influenced by communication in the work environment, namely communication from the leadership to the agent or communication between fellow agents must be created comfortable and friendly in order to cause a sense of family in the work environment, so that he becomes at home and excited in carrying out his duties. This study uses quantitative methods, which aims to determine whether there is an influence of leadership communication on agent performance, to determine whether there is an influence of work productivity on Agent Performance, and whether there is an influence of leadership communication and work productivity on Agent Performance at PT. Sun Life Financial Branch Medan City. Penelitain results obtained that the leadership communication variable (X) to work productivity (Y1) has a significant value of 0.000<0.05 and the value of leadership communication thitung of 10.931>1.658, so it can be concluded that H1 accepted which means there is an influence between the leadership communication variable (X)to work productivity variable (Y1), Leadership communication variable(X) to Agent achievement (Y2) has a significant value of 0.000<0.05 and the calculated value of 7.892>1.658 so that it can be concluded that H2 is accepted which means that there is an influence between leadership communication variable (X) to Agent achievement variable (Y2), simultaneous test shows that there is a significant value of leadership communication to work productivity of 0.000<0.05.